An improved screen force model based on CFD simulations of the hydrodynamic loads on knotless net panels. (January 2022) - Wang, Gang; Martin, Tobias; Huang, Liuyi; Bihs, Hans
Abstract: Knotless net panels are widely-adopted for traditional fish cages and offshore fish farms. A new screen force model based on numerical simulations of a portion of knotless net panels is proposed in this paper. At first, the hydrodynamic loads on knotless smooth and textile twisted net panels are studied using Improved Delayed Detached Eddy Simulations while varying the incoming velocity as well as the diameter and length of the net twines. The accuracy of the simulations is validated through a computational grid and domain independence study for the mean hydrodynamic loads on full-size net panels. The comparison of the hydrodynamic loads on a circular cylinder, cruciform and net panel reveals the unique hydrodynamics around net panels which emphasises the importance of studying complete panels. Then, a Kriging metamodel is established from the simulation-based data to generate response surfaces for the hydrodynamic load coefficients for a large range of flow and geometrical properties. Hence, this combination of high-fidelity CFD and Kriging metamodelling provides a more flexible approach than the common theoretical or experimental variations of screen force models. The metamodel predicts well the non-linear relation between drag coefficient, twine diameter and length of the twines. A second-order regression fitting is applied to generate a closed polynomial which is compared to existing approaches and physical measurements for validation. The proposed approach outperforms previous screen force models for the prediction of the drag and lift coefficients for a wide range of nets and inflow velocities due to the inclusion of different roughnesses and more geometrical properties of the net in the derivation. Finally, the proposed formula for the drag force coefficients is applied to a two-way coupled CFD method which is based on screen force models to determine the hydrodynamic loads. It can be shown that the new approach is superior to previously used screen force models for the simulation of the drag forces on and the velocity reduction behind net panels. Highlights: An improved screen force model based on CFD and Kriging methods firstly. Different net materials are included in new formula firstly. Extensive validations with experiments and existed screen models. Application to two-way fluid–structure coupling for hydrodynamics coefficients and velocity reduction of nets.